A Mixed-Longitudinal Study of Height Velocity of Greek Schoolchildren and the Milestones of the Adolescent Growth Spurt - Kleanthis Kleanthous; Dimitrios T. Papadimitriou; Alexandros Gryparis; Vassiliki Papaevangelou; Anastasios Papadimitriou (MDPI AG, 2022)
Height velocity (HV) growth charts constructed from longitudinal studies are scarce as they have inherent difficulties, e.g., time, and costs. These difficulties can be partly overcome by a mixed-longitudinal study that covers the entire age range within 3-6 years. To construct HV charts of Greek children and to estimate the milestones of the adolescent growth spurt (AGS), i.e., the onset of AGS (take-off), peak HV, and total pubertal growth (TPG), we performed a mixed longitudinal study in 1514 Greek schoolchildren (6-18 years) with height measurements every 6 months during three schoolyears. We constructed HV charts for boys and girls. Take-off occurs earlier in girls, and, in both sexes, it precedes by 1-1.5 years the appearance of physical signs of puberty. PHV in boys occurs at 12.61 years and in girls at 10.93 years. At take-off, boys are 5 cm taller than girls and TPG for boys is 35.8 cm and for girls 27.3 cm. We constructed HV charts plotted by age, irrespective of pubertal status, and presented data on the milestones of AGS. Furthermore, we suggest that the gradual increase in IGF-1 and E2 that occurs after 5 to 6 years of age triggers the onset of AGS, which precedes physical signs of puberty.